design and realization of a drone for optimizing the trajectory between two points - medaoui, rachid; sadallah, younes (universty of elouedجامعة الوادي, 2020)
تعد الطائرات بدون طيار أحد الوسائل المهمة في العديد من المجاالات ( التصوير الفوتوغرافي، صناعة االفالم ...الخ) ومع مرور الوقت تطور استخدامها في الوقت الحاضر بشكل رهيب حيث اصبحت تستعمل في مجاالت اخرى مثل البحث والتحري، التعرف على الوجه ...الخ. حيث ادى هذا االستخدام الواسع الى تطوير اساليب استعمال الطائرات بدون طيار وذلك بفضل خوارزميات الذكاء االصطناعي. ومن بينها خوارزميات التألية حيث اصبحت الطائرات بدون طيار ذاتية التحكم مما جعلها تتمتع بقدرات طيران جيدة و تتأقلم مع البيئة الموجودة فيها، اضافة الى خوارزميات تحسين التعرف على المسار والتي بدورها اصبحت تسلك أقصر مسار . ولهذا الغرض فإننا نهدف الى تصميم، نمذجة و تألية طائرة بدون طيار و التي تكون قادرة على الطيران و اتباع مسار محدد مسبقا. باستخدام تقنيتين رئيسيتين ، األولى هي الشبكة العصبية االصطناعية التي تُستخدم لتجنب العوائق والثانية هي خوارزمية البحث بأولوية االفضل للبحث عن أقصر مسار."Drones are considered one of the important tools in many fields (photography, film-making, etc.). Overtime their use has developed quickly nowadays, as they are used in other fields such as research and investigation, facial recognition ... etc. This widespread use has led to the development of methods of using drones due to the artificial intelligence algorithms. Among them are the machine learning and deep learning algorithms where drones have become autonomous, which makes them have good flight capabilities and adapt to the environment in which they are, in addition to the optimization algorithms, which give them the ability to cross a trajectory in shortest path. For this purpose, we aim to design, model and automate a drone that is able to fly and follow a predetermined path by using two main techniques, the first one is the artificial neural network which is used for the obstacle avoidance and the second one is the A* optimization algorithm to search for the shortest path. "
mémouer de fin master infourmatique
Keywords: طائرات بدون طيار، الذكاء االصطناعي، خوارزميات التألية.; Drones, artificial intelligence, facial recognition, machine learning, deep learning, and optimization algorithm